Kewajiban Dan Tanggung Jawab Notaris Sebagai Pejabat Umum - Triwahyuni, Abdullah Dian (Acta Comitas : Jurnal Hukum Kenotariatan, 2020)
The position of notary has been regulated in Act Number 2 of 2014 concerning Amendment to Law Number 30 of 2004 concerning Notary Position (hereinafter referred to as UUJN-P). Even so, philosophical and technical notary obligations and responsibilities are not regulated in detail in these laws and regulations, leading to the absence of a barometer that becomes a standard for notary behavior, notary office administration system, and notary office governance that applies universally. This has caused in some instances negative views on the notary profession in the community. One of the negative views is because the morality of the notary is not in tune with ethical behavior in society. Negative views also arise due to the administration of notary office administration and the layout of the notary office that does not meet the aesthetic element. The situation made the notary public seem unprofessional in providing social services in his function as a public official. Then what should be the notary morality? How about a good notary office administration? How should the notary manage his office? The writing of this article uses normative research using a positive legal approach and a conceptual approach. Sources of legal materials used are primary legal materials and secondary legal materials. Legal materials were analyzed using descriptive techniques. The results of this study indicate that there are not yet detailed and universal rules regarding the obligations and responsibilities of notaries sociologically and technically in providing social services, but the values ??that live and develop in society can be used as benchmarks for notary behavior and administrative systems notary office and notary office governance.